A Study of Clinico-pathological Profile of Suspected and Confirmed Neonatal Sepsis at Kathmandu Medical College - Shrestha, Anup; Shrestha, S (Nepal Medical College Journal, 2020)
Neonatal sepsis is a common reason for neonatal morbidity and mortality. Only clinical manifestations are inadequate to diagnose neonatal sepsis. In context of Nepal, there has been few studies correlating bacterial and clinical profile but none till now has managed to define the most adequate parameters to diagnose neonatal sepsis with certainty. Hence, this study is conducted to describe and compare clinical and laboratory characteristics of culture positive and clinically suspected sepsis (blood culture negative) and then assess whether differences exist between them. A descriptive prospective study was carried out for a period of one year starting from April 2017 to March 2018 at the NICU of Kathmandu Medical College. A total of 129 culture proven and suspected septic neonates were included. Clinical features, septic screening including blood culture, biochemical tests and radiological findings were taken into consideration. The incidence of definite neonatal sepsis was 22.4%. The most common bacterial isolates were gram negative bacteria. Klebsiella spp (48%) followed by CoNS (17%), Acinetobacter spp (14%), Enterobacter spp (7%), Pseudomonas (7%) and Staphylococcus aureus (7%) were isolated. Different non specific clinical features like respiratory and gastro-intestinal symptoms were seen. The neonates with clinical features had positive correlation with abnormal laboratory parameters with statistically significant p value, suggesting that septic neonates showed abnormal laboratory parameters. This data emphasizes the role of laboratory parameters other than blood culture for the diagnosis and empirical treatment of neonatal sepsis.